The Formation Models of Gypsum Barrier, Chemical Temporal Changes and Assessments the Water Quality of Sawa Lake, Southern Iraq - Awadh, Salih; Muslim, Ruaa (Iraqi Journal of Science, 2023)
This study deals with formation models of gypsum barrier, chemical temporal changes, and assessments of the Sawa Lake within the Al- Muthanna province, Southern Iraq, it is a very important issue to find the water quality and water assessments of this lake. Eleven water samples are collected from Sawa Lake. Many scientific concepts are used such as major cations (Ca2+, Mg2+, Na+ and K+), major anions (SO4=,Cl-,HCO3- and CO3=) with minor anions ( PO43-, NO3-) and H2S . Trace elements (Pb, Cd, Zn, As, Ni, Co, Cu, Mn, Fe, As, Sr And B) and bacterial test were analyzed in each sample. Total dissolved solids (TDS), electrical conductivity (EC), pH and temperature (T) were directly measured in the field. The equilibrium state between the concentration and evaporation contributed actively to build the salt wall surrounded the lake. The building wall of the Lake is a barrier of gypsum, which is in a dynamic state between construction and dissolution.The length of gypsum barrier surrounding the lake is 12.5 km with 3-6 m high. Gypsum wall collapse occurs in abundance in the sites that face the wind which activates the erosion processes.The chemistry of Sawa Lake during 1977, 1983 and 2003 was Na- SO4=; then it was changed to be as Mg-Cl from during 2007and 2011 (present study). This study revealed that theSawa Lake water is as unsuitable for drinking, livestock and irrigationpurposes.